If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6(m + 2) = 30 Reorder the terms: 6(2 + m) = 30 (2 * 6 + m * 6) = 30 (12 + 6m) = 30 Solving 12 + 6m = 30 Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-12' to each side of the equation. 12 + -12 + 6m = 30 + -12 Combine like terms: 12 + -12 = 0 0 + 6m = 30 + -12 6m = 30 + -12 Combine like terms: 30 + -12 = 18 6m = 18 Divide each side by '6'. m = 3 Simplifying m = 3
| 11/9*33/5= | | X=(2x+8)+(3x-4) | | 1/9*3/5= | | 185x*45y+60y=10500x | | 3x-12+x=124 | | -2(-6a-4)-2=-90 | | 8z-72=8 | | 6x^5+17x^4-x^2+3x+3=0 | | 6+4x=-4x+22 | | 4(x-2)=-3(5-x) | | 5x+2x-8=41 | | Z^2=8-8i | | 5x-6+3=7 | | 5x+2x-8=42 | | 15x=17+8x-24 | | -19=13x+2 | | 6c+3+11=8c | | 45x+60x+185y=10500 | | 0.5y+9=31 | | 3.96=-44z | | X+(-5)=18 | | 0.5y+9= | | -2.5x-1.7=-16.4 | | 3x+2(x+7)=86 | | 3x-5-x+2=13 | | 8.5=4x+5 | | X+(-4)=-25 | | 2x-5=64 | | -4t+24=16 | | 49x+1=48x+3 | | 2.86-21.1= | | (-18)=5x-8 |